2020
DOI: 10.1093/jas/skaa366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal organic selenium supplementation during pregnancy on sow reproductive performance and long-term effect on their progeny

Abstract: Selenium (Se) is an essential trace element for animals, and exists in nature in both inorganic and organic forms. Although organic Se is more bioavailable than inorganic Se, there are inconsistent reports on the effect of organic Se on the reproductive performance of sows. This study was conducted to investigate the effect of maternal organic Se (2-hydroxy-4-methylselenobutanoic, HMSeBA) supplementation on reproductive performance and antioxidant capacity of sows, and the long-term effect on the growth perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 64 publications
3
26
0
Order By: Relevance
“…Studies have shown that HMSeBA to be more bioavailable than sodium selenite or selenium yeast in poultry, growing pigs and weaned pigs [12][13][14][15]. Our lab also found HMSeBA supplementation during sow pregnancy increased the number of total born piglets, decreased the piglet birth interval, improved concentrations of total selenium, and also improved activity of antioxidant enzymes compare with the control and sodium selenite treatment [16]. However, the available data concerning HMSeBA action on the gilts' reproduction and function on the granulose cells remain insufficient.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Studies have shown that HMSeBA to be more bioavailable than sodium selenite or selenium yeast in poultry, growing pigs and weaned pigs [12][13][14][15]. Our lab also found HMSeBA supplementation during sow pregnancy increased the number of total born piglets, decreased the piglet birth interval, improved concentrations of total selenium, and also improved activity of antioxidant enzymes compare with the control and sodium selenite treatment [16]. However, the available data concerning HMSeBA action on the gilts' reproduction and function on the granulose cells remain insufficient.…”
Section: Introductionsupporting
confidence: 54%
“…We found that the age and weight of puberty in DLY gilts were higher than those in LY gilts (220-250d vs. 190-210d, 120-140kg vs. 105-120kg, Zhou et al, 2010) [22]. In the current study, the gilts were applied the same treatments with their maternal generation during gestation [16]. Dietary supplementation with HMSeBA increased the average daily body weight gain (ADG) and decreased the ratio of feed: gain during day 120 to 176 in gilts.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In total, 12, 11 and 10 studies included data on selenium content in colostrum (WMD = 0.063, 95% CI [0.041, 0.085], P < 0.01, I 2 = 89.2%), selenium content in milk (WMD = 0.035, 95% CI [0.019, 0.052], P < 0.01, I 2 = 99.3%) and selenium content in sow serum (WMD = 0.010, 95% CI [0.003, 0.017], P < 0.01, I 2 = 90%), respectively. There were 14 studies that mentioned the effect of Yue, 2012 Yoon and McMillan, 2006Xu, 2017Wang and Yang, 2013Szuba-Trznadel et al, 2017Svoboda et al, 2009Svoboda et al, 2008Quesent et al, 2008Mou et al, 2020bMou et al, 2020aMahan and Kim, 1996Mahan and Peter, 2004Mahan, 2000Ma et al, 2014Lin et al, 2013Li, 2009Jia, 2012Falk et al, 2020 organic and mineral selenium source on selenium content in piglet serum (WMD = 0.033, 95% CI [0.014, 0.052], P < 0.01, I 2 = 99.5%), and eight studies measured the GSH-Px activity in piglet serum (WMD = 0.044, 95% CI [0.004, 0.085], P < 0.05, I 2 = 87.5%). Figure 6 shows a forest plot summarizing the above data.…”
Section: Heterogeneity Test and Statistical Analysismentioning
confidence: 99%
“…The effectiveness of this new organic selenium source in poultry, growing pigs, and sows has been reported (Jlali et al, 2013;Chao et al, 2019). Adding HMSEBA in the diet of sows can improve the antioxidant capacity of sows and their offspring (Mou et al, 2020a). However, the effect of HMSeBA on gilts has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%